Statistics Using Python - Campesato, Oswald (Mercury Learning and Information, 2024)
This book is designed to offer a fast-paced yet thorough introduction to essential statistical concepts using Python code samples, and aims to assist data scientists in their daily endeavors. The ability to extract meaningful insights from data requires a deep understanding of statistics. The book ensures that each topic is introduced with clarity, followed by executable Python code samples that can be modified and applied according to individual needs. Topics include working with data and exploratory analysis, the basics of probability, descriptive and inferential statistics and their applications, metrics for data analysis, probability distributions, hypothesis testing, and more. Appendices on Python and Pandas have been included. From foundational Python concepts to the intricacies of statistics, this book serves as a comprehensive resource for both beginners and seasoned professionals. FEATURESProvides Python code samples to ensure readers can immediately apply what they learnCovers everything from basic data handling to advanced statistical conceptsFeatures downloadable companion files with code samples and figuresIncludes two appendices, An Introduction to Python and an Introduction to Pandas as refresher material